Analisis Tingkat Pertumbuhan Penjualan, Kompensasi Rugi Fiskal, dan Capital Intensity Terhadap Penghindaran Pajak - Muhammad Zufar, Luki; Fitri Arianti, Baiq (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2023)
This study aims to determine the Analysis of Sales Growth Rate, Fiscal Loss Compensation, and Capital Intensity on Tax Avoidance (Empirical Study on LQ45 Companies listed on the Indonesia Stock Exchange for the 2017-2021 period) both partially and simultaneously. This type of research is quantitative. The samples in this study were obtained using purposive sampling techniques, so that 20 samples were obtained with the 2017-2021 research period. The data used in this study was obtained from financial statements. The tests used in this study are descriptive statistical tests, selection of panel data regression estimation models, classical assumption tests, and hypothesis tests. To answer the research problem, the data was analyzed using the Eviews 9 tool. The result of this study is that based on a partial test of sales growth has an effect on tax avoidance, fiscal loss compensation has no effect on tax avoidance, and capital intensity has an effect on tax avoidance.